L’erouv de Jérusalem - Calle, Sophie (CV Photo, 2001)
According to Jewish law, complete rest is obligatory during Shabbat. The ban on working includes carrying any objects (keys, a book, a bag) outside the home. However, according to the Torah, a village or city surrounded by a wall with gates is considered a private domain. Today, it is an accepted practice to "build" eruvim using wire, string, or galvanized-steel ropes to form an imaginary wall. I asked residents of Jerusalem, Israeli and Palestinian, to take me to a public space that has, in their eyes, a private character.